Interval analysis and automatic result verification - Mayer, Günter 1951- (De Gruyter, 2017)
This self-contained text is a step-by-step introduction and a complete overview of interval computation and result verification, a subject whose importance has steadily increased over the past many years. The author, an expert in the field, gently presents the theory of interval analysis through many examples and exercises, and guides the reader from the basics of the theory to current research topics in the mathematics of computation. Contents Preliminaries Real intervals Interval vectors, interval matrices Expressions, P-contraction, ε-inflation Linear systems of equations Nonlinear systems of equations Eigenvalue problems Automatic differentiation Complex intervals
Keywords: Automatische Differentiation; Computerarithmetik; Intervalalgebra; Intervalanalyse; Richrigkeit von Ergebnissen; Intervallalgebra; Richtigkeit von Ergebnissen